Some Critical Aspects of Hunting as Sport - Postić Bezenšek, Vilma Alina (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Hunting has been an integral component of human societies for millennia, initially serving as a primary means of subsistence before evolving into recreational and sport-based practices in many parts of the world. In contemporary conservation debates, hunting remains a controversial yet significant topic, particularly in relation to sustainability and wildlife management. This article explores the concept of hunting as a sport within the framework of sustainable development, examining its ecological, economic and social dimensions. Drawing upon existing literature in wildlife management, conservation biology and environmental policy, the paper evaluates whether regulated sport hunting can contribute to biodiversity conservation and sustainable ecosystem management. The analysis highlights the potential benefits of controlled hunting, including wildlife population management, habitat conservation and the generation of financial resources for conservation initiatives. At the same time, it critically addresses ethical concerns, governance challenges and ecological risks associated with unsustainable hunting practices. The findings suggest that while hunting alone cannot resolve global biodiversity challenges, it can function as a complementary conservation tool when integrated into science-based management systems, supported by effective regulations and inclusive community participation.